Isotopic evidence for Last Glacial climatic impacts on Neanderthal gazelle hunting territories at Amud Cave, Israel. Issue 84 (July 2015) - Hartman, Gideon; Hovers, Erella; Hublin, Jean-Jacques; Richards, Michael
Abstract: The Middle Paleolithic site of Amud Cave, Israel, was occupied by Neanderthals at two different time periods, evidenced by two chronologically and stratigraphically distinct depositional sub-units (B4 and B2/B1) during MIS 4 and MIS 3, respectively. The composition of both hunted large fauna and naturally-deposited micromammalian taxa is stable at the site over time, despite a ∼10 ky gap between the two occupation phases. However, while gazelle is the most ubiquitous hunted species throughout the occupation, isotopic analysis showed that there is a marked change in Neanderthal hunting ranges between the early (B4) and late (B2/B1) phases. Hunting ranges were reconstructed by comparing oxygen, carbon, and strontium isotopes from gazelle tooth enamel with modern isotope data from the Amud Cave region. This region is characterized by extensive topographic, lithological, and pedological heterogeneity. During the early occupation phase negative oxygen isotope values, low radiogenic 87 Sr/ 86 Sr ratios, and low Sr concentrations reveal restricted gazelle hunting in the high elevations west of Amud Cave. In the late occupation phase, hunting ranges became more diverse, but concentrate at low elevations closer to the site. Climatic proxies indicate that conditions were drier in the early occupation phase, which may have pushed gazelle populations into higher, more productive foraging areas. This study showed that Neanderthals adjusted their hunting territories considerably in relation to varying environmental conditions over the course of occupation in Amud Cave. It highlights the utility of multiple isotope analysis in enhancing the resolution of behavioral interpretations based on faunal remains and in reconstructing past hunting behaviors of Paleolithic hominins.